Intussusception in a 4-Year-Old Male Due to Burkitt Lymphoma - Raed Al-Taher; Abdallah Alabadla; Salameh Al-Halaseh; Ghasaq Saleh (Case Reports in Pediatrics)
Intussusception is the invagination of a proximal bowel segment into a distal segment causing bowel obstruction, especially in children. In some cases, it can be caused by a pathological lead point, such as Burkitt lymphoma. Burkitt lymphoma has several patterns of clinical presentations, such as jaw or facial bone tumor in the endemic form, in contrast to an abdominal presentation most often with massive disease and ascites. We describe a case of a 4-year-old male who presented bowel obstruction. Using X-ray and ultrasound findings, ileocecal intussusception was then diagnosed. Resection and anastomosis was performed after multiple trials of failed hydrostatic reduction. On the pathology report of the resected segment, Burkitt lymphoma was found to be the cause and chemotherapy was initiated. The patient is doing well and is following up every 6 months for 2 years. A pathological lead point, especially Burkitt lymphoma, should be suspected in patients with failed conservative treatment, and prompt diagnosis of the pathology should be performed to prevent further sequela of the disease.